Technical skills leading in winning or losing volleyball matches during Beijing Olympic Games - Patsiaouras, A.; Moustakidis, A.; Charitonidis, K.; Kokoridas, D. (Journal of Physical Education and Sport, 2011)
Volleyball is included in sports where individual success of final efforts such as a successful attack or an effective block, is achieved by the harmonious collaboration of the preceded players` efforts. The purpose of this present study was to evaluate the importance of technical skills that led to the success of the national teams that took part in the Olympic Games of Beijing 2008. The sample was constituted by all the matches of the volleyball men teams that participated in the Beijing Olympic Games. Overall, 29 games were videotaped and evaluated. Collection of data included the use of the statistical recording program Data Volley 2. The parameters that were evaluated were: a) service, b) service reception, c) attack, and d) attack blocked. The statistical treatment of data was realised through non parametric statistical analysis. The results showed that, service points, reception errors, and attacks blocked emerged as important factors that were decisive for wining or losing a match.